If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g+3/7=2/7
We move all terms to the left:
g+3/7-(2/7)=0
We add all the numbers together, and all the variables
g+3/7-(+2/7)=0
We get rid of parentheses
g+3/7-2/7=0
We multiply all the terms by the denominator
g*7+3-2=0
We add all the numbers together, and all the variables
g*7+1=0
Wy multiply elements
7g+1=0
We move all terms containing g to the left, all other terms to the right
7g=-1
g=-1/7
g=-1/7
| w/2-4=5 | | s3+5=3 | | 73=n+13 | | x/12=8.12 | | 2/3-4x+7/2=-9x | | 44x-6=64 | | 2x-3x=5x-5 | | 6+6d=12+14 | | 13v=56+6v | | z-22=15 | | 3*(3x-2)²=66 | | 15v-9v=30 | | 2x+36=74 | | 4(2x−1)+2x+2=28 | | (5x+17)+(13x+17)=180 | | 7k-3k=+11 | | 3(2x+4)-2x+1=17 | | (6x+1)+(2x+10)+79=180 | | 3x+25+4x-19=180 | | -8.5x+0.85=5.95 | | -18+2x=x+16 | | -18+2x=x+1 | | 3(2x+4)-2x+1=3(2+4)−2x+1= | | x/8-x/4=5 | | 8x−12=4(1/2x−6) | | x/8−x/4=5 | | x8−x4=5 | | (7a+2)-(2a-4)=65a | | n=((6-5n)((6-5n)+1))/2 | | 2(7z-7)=2(7z−7)=14 | | −6+5y=−3(2−y) | | -5.3w+8.0w-11.6=14-25.6+2.7w |